(untitled) (Research, Society and Development, 2019)
Due to the lack of sanitation services in rural areas, this study aimed to analyze the basic sanitation scenario, regarding water supply and sanitary sewage disposal, in the rural community of Capela Branca, in Bela Vista de Minas - MG. First, a questionnaire was applied to 10 families who live in the community and are supplied by one of the springs located in the place, in order to characterize the residents’ opinion regarding sanitation, as well as the social and cultural conditions of the community; subsequently, physical-chemical and microbiological analyzes were carried out on water samples from the source in question; Finally, alternative solutions were suggested for the treatment of water and sewage in the community. Through the questionnaire applied it was possible to verify that a portion of the population can see that the deprotection and the proximity of the water course under study with contaminating sources, can interfere in the quality of the water. Through the water analysis it was verified that the parameters color and turbidity are in concentrations higher than the maximum values allowed by Ministry of Health Ordinance 2914/2011, in addition to the presence of total coliforms and Escherichia coli. In relation to the water treatment, it was suggested the combination between the Moringa Oleífera seed and the solar radiation, as for the sanitary sewage arrangement, it was suggested the use of systems such as the evapotranspiration tank, built floodwaters, biodigestory septic tank and circle of banana trees. It was concluded that the site is lagged in relation to water and sewage systems, which can spread diseases to the residents, besides causing environmental impacts, necessitating improvement of rural sanitation infrastructure.